Conclusions and future prospects - Junidah, Lamaming; Abu Zahrim, Yaser; Daniel, Johnson; Nidal, Hilal (Elsevier Inc., 2025)
Nutrient and color pollutants have increased in parallel with population growth and rapid development in Industry Revolution 4.0. Managing and recovering the nutrients, as well as color removal from wastewater, is essential to achieving sustainable development goals. Economically feasible, technically viable and socially feasible nutrient recovery and color removal strategies from wastewater must be established for safe and clean water in the future.